Seroprevalence and Serotypes of Dengue Virus Infection in Ghana: A Systematic Review and Meta-Analysis - Isaac Boamah; Alex Odoom; Kwamena W. C. Sagoe; Eric S. Donkor (Diseases)
Background: Dengue virus (DENV) infection poses a serious and growing public health threat in many tropical and subtropical regions worldwide, including Ghana. Despite the heightened risks due to suitable climatic conditions and the presence of competent vectors, the epidemiology of DENV in Ghana remains poorly understood, underscoring the critical need for a comprehensive assessment of the burden and circulation of the virus in the country. Methods: The review was conducted in accordance with the PRISMA guidelines. A literature search was conducted using the PubMed, Web of Science, and Scopus databases from inception to 24 September 2024. Studies presenting primary DENV seroprevalence data among Ghanaian populations were included. Quality was assessed using JBI tools. Meta-analyses estimated pooled prevalence with 95% CIs using random-effects models. Heterogeneity was evaluated using I2 statistic. Results: A total of nine studies met the selection criteria, with eight studies involving febrile patients and one involving blood donors. The pooled seroprevalence rates were 33.3% (95% CI: 16.2–50.4%) for IgG, 5.9% (95% CI: 0–12.5%) for IgM, 1.5% (95% CI: 0.4–2.6%) for DENV RNA, and 32.3% (95% CI: 0–68.5%) for IgG/IgM combined. Notably, the IgG seroprevalence exhibited substantial heterogeneity (I2 = 99%). DENV-2 and DENV-3 were the predominant serotypes identified. There was potential bias in seroprevalence estimates from hospital-based febrile samples. Conclusions: This review has established the prevalence and circulation of DENV serogroups in Ghana. The higher seropositivity and heterogeneity underscore the need for standardized large-scale surveillance to optimize disease characterization and guide control. Integrating dengue prevention into existing vector control programs could help reduce risks in Ghana.